Collaboration with local health centers in the development of a Level I Obstetric Ultrasound Workshop for radiology trainees - Samedra, Rovi Niño D.
Ultrasound imaging is the primary diagnostic modality used to evaluate obstetric patients. With the advent of Point-of-Care ultrasound (PoCUS), there has been an increasing interest of clinical practitioners, like obstetricians, to perform ultrasound on their patients. This has led to the decline in referrals for ultrasound evaluation for the post-graduate trainees of the Radiology Department. Of all the organ systems, the most notable decline in referral to the department is for obstetric ultrasound, as most training institutions of obstetrics has their own ultrasound fellowship training. This decline in patients seen by radiology trainees corresponds to a decline in this competency among our ranks, despite the availability of the machines and experts in the field. A proposed solution to this dilemma is by collaborating with the local health centers: providing obstetric ultrasound for their pregnant patients, and also supplement the number of cases seen by the trainees.